The modal realism of David Lewis - Sullivan, Andrew (My University, 1996)
It seems everyone who encounters David Lewis's modal real ism finds it utterly strange. I attempt to show that it is strange because it expands our onto logy unnecessarily.
I begin by situating Lewis in the tradition of understanding modality with the help of possible worlds. I go on to indicate the internal tensions which arise under Lewis's view when we consider sane kinds of perfectly normal modal discourse. T try to show that the problem comes from an understanding of existence which is quite common in analytic philosophy. I then suggest a way of understanding modal language which finds its inspiration in the writings of st Thomas Aquinas, Ludwig Wittgenstein, and Donald Davidson.
Keywords: Philosophy; Philosophy